Effect of paclobutrazol on growth retarding in potted chrysanthemum (Dendranthema grandiflora) - Piphatwatthanakul, P.; Boonkamjat, T.; Saetiew, K. (My University, 2024)
Paclobutrazol application was compared to the control. It showed a positive influence in reducing stem height, canopy width, internode length, node number, and flower size. Besides, methods of application were insignificantly found. As for the second experiment, decreased concentrations to 0, 100, 200, 300, and 400 ppm of paclobutrazol were tested, using the same manner of application as in the first experiment. It appeared that all concentrations of paclobutrazol decreased canopy width, stem length, internode length, and node number when compared with the control treatment, similar to results of the experiment 1. Nevertheless, it occurred in Prakaimat variety that both foliar spraying and soil drenching of paclobutrazol led to increasing chlorophyll content and carotenoid level. Meanwhile, Fiona chrysanthemum responded better to foliar spraying method than of soil drenching.
Keywords: Chlorophyll; Foliar spraying; Morphology; Plant growth regulator; Soil drenching